The determinants of gold price in Malaysia / Nur Farahin Saat - Saat, Nur Farahin (Faculty of Business and Management, 2014)
The purpose of the study is to determine the determinants of gold price in Malaysia in order to investigate whether the gold price in consumer product will be affected by the factors. Even the economic condition is bearish such as financial crisis is happening, but the demand from consumer product sector will be there. The determinants will be chosen to be analyzed. The data that will be used is crude oil price, exchange rates, inflation rates and silver price. Multiple regression models will be used to identify any significant differences among the variables. The dependent variable is the gold price while the independent variable is the crude oil price, inflation rates, exchange rates and silver price.